2013
DOI: 10.1541/ieejfms.133.32
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pulse Width on Polyphenol Extraction from Agricultural Products by Pulsed Electric Field

Abstract: Effect of a pulsed electric field (PEF) on polyphenol extraction from grape skins in water was investigated experimentally. The grape skins were immersed in the distilled water between plate-to-plate electrodes in a rectangular shaped reactor. The pulsed voltage was generated by pulse forming network (PFN) to control a pulse width of the high-voltage applied to the plate electrode.The total polyphenol extracted from the grape skins was evaluated as gallic acid using the Folin-Ciocalteu method. The grape skins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…The microscopic observation showed that membranes of anthocyanoplasts were raptured by PEF exposure, and the red-colored pigments in the anthocyanoplasts were extracted into the cell and solvent, as shown in Figure 29 . The polyphenol extraction was enhanced with an increasing pulse width in the PEF treatment, i.e., the energy required for polyphenol extraction decreased with an increasing pulse width, as shown in Figure 30 [ 69 ].…”
Section: Pef Poration Process Of Cell Membranes and Its Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The microscopic observation showed that membranes of anthocyanoplasts were raptured by PEF exposure, and the red-colored pigments in the anthocyanoplasts were extracted into the cell and solvent, as shown in Figure 29 . The polyphenol extraction was enhanced with an increasing pulse width in the PEF treatment, i.e., the energy required for polyphenol extraction decreased with an increasing pulse width, as shown in Figure 30 [ 69 ].…”
Section: Pef Poration Process Of Cell Membranes and Its Applicationsmentioning
confidence: 99%
“… Increased rates of polyphenol extraction by PEF treatment for different pulse widths compared to water extraction at the same temperatures [ 69 ]. © The Institute of Electrical Engineers of Japan 2013.…”
Section: Figurementioning
confidence: 99%
“…The PEF extraction efficiency is affected by the PEF conditions (e.g. pulse width, input energy, etc), as shown in figure 51 [202].…”
Section: Extraction Of Intracellular Contents For Food Processingmentioning
confidence: 99%
“…PEF treatment enhanced compression kinetics and extraction of polyphenols from Chardonnay grapes [45]. PEFassisted extraction of polyphenols from grape skins by water was investigated experimentally [50]. A microscopic observation has clearly shown that PEF treatment invoked extraction of red color pigments from anthocyanoplasts into the cell.…”
Section: Grapesmentioning
confidence: 99%